2014
DOI: 10.1039/c4cp02660h
|View full text |Cite
|
Sign up to set email alerts
|

A semiconductive superhard FeB4phase from first-principles calculations

Abstract: An oP10-FeB4 phase [H. Gou, et al., Phys. Rev. Lett., 2013, 111, 157002] was recently synthesized based on previous theoretical predictions. In this study, a high-pressure phase of FeB4 (tP10-FeB4) was proposed through first-principles calculations. The tP10-FeB4 structure, which contains two formula units per unit cell, belongs to tetragonal symmetry with the space group P42/nmc. The boron atoms in tP10-FeB4 are present as tetrahedron configurations. Enthalpies as a function of pressure indicate that this new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…1. The FeB 4 phases with P4 2 /nmc and I4 1 /acd space groups have also recently been found by Wang et al 34 and Kotmool et al, 35 respectively. Previous experimental and theoretical results obtained metal tetraborides for 58-, hp20-, 71-, 59-, and 194-FeB 4 ; these are also shown in Fig.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…1. The FeB 4 phases with P4 2 /nmc and I4 1 /acd space groups have also recently been found by Wang et al 34 and Kotmool et al, 35 respectively. Previous experimental and theoretical results obtained metal tetraborides for 58-, hp20-, 71-, 59-, and 194-FeB 4 ; these are also shown in Fig.…”
Section: Resultssupporting
confidence: 57%
“…3 shows the energy differences of the static lattices of hp20-, 59-, 194-, 229-, 216-, 64-, 187-, 137-, and 142-FeB 4 , relative to the 58-FeB 4 phase as reference. 34 It is worthy to mention that 58-FeB 4 , 194-FeB 4 and 59-FeB 4 have similar layered structures. Then, a tetragonal 142-FeB 4 phase (II) takes over in the pressure range from 55 to 695 GPa, followed by a cubic 229-FeB 4 phase (III) at higher pressures above 695 GPa.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Li et al [8] calculated the thermodynamic properties of FeB 2 in 2014. Wang et al [9] calculate the Vickers hardness (H v ) of the oP12-FeB 2 by first-principles calculations, which confirms that the oP12-FeB 2 has reached the super hard standard (H v >40 GPa). Gou et al [7] however, have demonstrated by the first principles calculations that the oP12-FeB 2 is a high hardness material with a value of 32.1 GPa.…”
Section: Introductionmentioning
confidence: 87%
“…More recently, a metal-to-semiconductor phase transition for OsB 4 at high pressure was predicted by Kotmool et al, and a novel high-pressure tetragonal phase (space group P 4 2 / nmc , Z = 2, hereafter denoted as TR) with a band gap of 2.0 eV was uncovered for stabilizing at 11 GPa compared to the ground state of Pmmn -OsB 4 . Such a novel tetragonal TR phase was previously also proposed as a competitive high-pressure candidate for Pnnm -FeB 4 . , TR-OsB 4 is considered to be a promising superhard semiconducting material with a high calculated hardness of 60 GPa, originating from its larger shear modulus compared to those of Pnnm -FeB 4 and Pnnm -CrB 4 . Nevertheless, it is somewhat surprising that the calculated shear modulus (313 GPa) of TR-OsB 4 is larger than the calculated bulk modulus (289 GPa).…”
Section: Introductionmentioning
confidence: 99%